A Study on Students' Cognitive Development in Answering English Task - Agustina, Agustina; Ahmad, Muhammad Yusuf (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2020)
This study focuses on students’ cognitive development in answering English tasks based on Piagetian theory. The design of this study is descriptive quantitative with a pilot study to ensure that the tasks are reliable and valid. The subject of this study were 26 students at the third grade of MIN 3 Pekanbaru. While the object of this study is the students’ cognitive development. Data collection techniques used in this study are tests and documentation. Data analysis techniques used are editing, coding and tabulating. After conducting the study, the authors found conclusions on the students’ cognitive development at the third grade of MIN 3 Pekanbaruare in various levels, namely seriation (57.69%), transitivity (43.59%), composition (65.38%), decentering ( 50.00%), reversibility (52.56%), elimination (61.54%) and egocentrim elimination (24.36%). After calculation, the average of students’ cognitive development is in the medicore level (50.73%), whereas their agesare in the middle of the concrete operation stage, that is between 8 and 9 years old.